Deep R-gene discovery in HLB resistant wild Australian limes uncovers evolutionary features and potentially important loci for hybrid breeding - Liu, Jianyang; Singh, Khushwant; Huff, Matthew; Gottschalk, Christopher; Do, Michael; Staton, Margaret; Keremane, Manjunath L.; Krueger, Robert; Ramadugu, Chandrika; Dardick, Chris (Frontiers in Plant Science, 2025)
Huanglongbing (HLB) is a devastating citrus disease that threatens the citrus industry worldwide. HLB is associated with the bacteria Candidatus Liberibacter asiaticus (CLas) and as of today, there are no tools for economically viable disease management. Several wild Australian limes have been identified to be HLB resistant and their resistance is hypothesized to be conferred by resistance genes (R-genes), which mediate pathogen-specific defense responses. The aim of this study was to gain insight into the genomic features of R-genes in Australian limes, in comparison to susceptible citrus cultivars. In this study, we used five citrus genomes, including three Australian limes (Citrus australasica, C. glauca and C. inodora) and two cultivated citrus species (C. clementina and C. sinensis). Our results indicate up to 70% of the R-genes were identified in the unannotated regions in the original genome annotation of each species, owing to the use of a R-gene specific pipeline. Surprisingly, the two cultivated species harbored 15.8 to 104% more R-genes than the Australian limes. In all species, over 75% of the R-genes occurred in clusters and nearly 80% were concentrated in three chromosomes (Chr3, 5 and 7). The syntenic R-gene based phylogenic classification grouped the five species according to their HLB-resistance levels, reflecting the association between these R-genes and their distinct Australian origins. Domain structure analysis revealed substantial similarities in the R-genes between wild Australian limes and cultivated citrus. Investigation of chromosomal sites underlying Australian specific R genes revealed diversifying selection signatures on several chromosomal regions. The findings in this study will aid in the development of tools for genome-assisted breeding for HLB-resistant varieties.